Upaya Meningkatkan Keterampilan Berkomunikasi pada Anak Melalui Metode Bermain Peran - Noviyanti, Ade Irma; Ashadi, Firman; Kurnia, Nury; Aja, Susana (JOEAI (Journal of Education and Instruction), 2020)
This study aims to find out the influence of role-playing methods on communication skills in children in TK Labschool IKIP PGRI Jember. This type of research is Class Action Research (PTK) which consists of two cycles. Each cycle through the steps of Planning, implementation, observation, and reflection. This study focused on A2 group of 15 children. The results of this study revealed that children's communication skills have changed significantly in a positive direction. This can be seen from the change in average grades of students who increase and have a score of four stars (capable), cycle I grades get four stars (capable)13.3% and cycle II average score of 86.6% so it can be stated that role playing methods can improve the communication skills of children of group A2 in Labschool IKIP PGRI Jember. In conclusion, the method of playing the role of efektfif improves the communication ability of children in TK PGRI Jember significantly. Keywords: Role Playing, Communication Skills, Learning Methods